Orientation Control of Block Copolymer Thin Films Placed on Ordered Nanoparticle Mono layers - Kim, Taehee; Wooh, Sanghyuk; Son, Jeong Gon; Char, Kookheon (AMER CHEMICAL SOC, 2013)
We investigate orientation and lateral ordering of poly(styrene-block-methyl methacrylate) (PS-b-PMMA) diblock copolymer (diBCP) thin films placed on ordered nanoparticle (NP) monolayers. The densely packed NP monolayers were prepared on silicon substrates with the Langmuir-Blodgett (LB) deposition technique. The perpendicular domain orientation of BCP thin films is obtained on the ordered NP monolayers due to the nanoscale regular roughness which exerts the elastic deformation on the BCP nanodomains and suppresses the substrate-induced parallel orientation. The effect of BCP film thickness as well as the NP size on the orientation of BCP nanodomains was systematically investigated. We also demonstrate the defect-tolerant ordering perpendicular orientation of BCP thin films on the NP-vacant sites.
Keywords: LITHOGRAPHY; ARRAYS; GRAPHENE; LAMELLAE